Regioisomeric Effects of Donor–Acceptor–Acceptor′ Small‐Molecule Donors on the Open Circuit Voltage of Organic Photovoltaics. Issue 37 (25th July 2016) - Che, Xiaozhou; Chung, Chin‐Lung; Liu, Xiao; Chou, Shu‐Hua; Liu, Yi‐Hung; Wong, Ken‐Tsung; Forrest, Stephen R.
Abstract : Donor–acceptor–acceptor′ small‐molecule donors are synthesized to investigate regioisomeric effects on organic photovoltaic device performance. Cross‐conjugation in 2‐((7‐( N ‐(2‐ethylhexyl)‐benzothieno[3, 2‐ b ]thieno[3, 2‐ d ]pyrrol‐2‐yl)benzo[ c ][1, 2, 5]thiadiazol‐4‐yl)methylene)malononitrile leads to an increased open‐circuit voltage compared with its isomer 2‐((7‐( N ‐(2‐ethylhexyl)‐benzothieno[3, 2‐ b ]thieno[2, 3‐ d ]pyrrol‐2‐yl)benzo[ c ][1, 2, 5]thiadiazol‐4‐yl)methylene)malononitrile. A correlation is then established between molecular conjugation length and orbital energies, and hence open‐circuit voltage.